2015
DOI: 10.1515/acph-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Differences in antioxidant properties of ginkgo leaves collected from male and female trees

Abstract: Differences in antioxidant properties of ginkgo leaves collected from male and female treesTotal phenolic content and antioxidant capacity (FRAP method) of Ginkgo biloba L. leaves collected from male and female trees were determined and compared. Different water and aqueous ethanolic (water/ethanol 80/20, V/V) extracts were prepared by varying the time of infusing, boiling and steeping in order to determine the effect of the extraction method on the above parameters. Antioxidant activity and phenolic content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
(7 reference statements)
1
9
0
2
Order By: Relevance
“…A positive correlation between total phenolic content and free radical scavenging activity has been reported earlier also (Koczka et al, 2015). Thus, it can be inferred that the polyphenolics present in Gethi (Boehmeria rugulosa) contribute to the antioxidant property.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…A positive correlation between total phenolic content and free radical scavenging activity has been reported earlier also (Koczka et al, 2015). Thus, it can be inferred that the polyphenolics present in Gethi (Boehmeria rugulosa) contribute to the antioxidant property.…”
Section: Resultssupporting
confidence: 66%
“…They also reported that extracts with highest antioxidant activity have the highest concentration of phenolic acids also. Numerous other studies also mention that phenolic content of plants may contribute directly to their antioxidant action (Koczka et al, 2015;Tosun et al, 2009;Stankovic, 2011). Thus, phenolic compounds are potentially health promoting due to their antioxidant property.…”
Section: Resultsmentioning
confidence: 99%
“…Analizując przeprowadzone bada nia, można stwierdzić, że żółte liście miłorzębu japońskiego, które zakończyły wegetację, charakteryzują się dużą zdolnością zmiatania wolnych rodników, co potwierdzają wyniki zamiesz czone w tabeli 1. Na taką ich zdolność wskazują również bada nia innych autorów z wykorzystaniem liści miłorzębu [13,14,15,23,24], a także badania przeprowadzone na liściach innych roślin, w tym np. winorośli właściwej [25], aronii czarnej [26], akki sellowej [27], bielunia surmikwiatu [28] czy jeżyny euro pejskiej [29].…”
Section: Dyskusjaunclassified
“…Polife nole są cennymi składnikami roślinnymi, które mają wpływ m.in. na proces zmiatania wolnych rodników, co wyraża się dodatnią korelacją pomiędzy ich zawartością a właściwościami antyoksydacyjnymi liści miłorzębu [14,23,35]. Potwierdzają to badania własne, w których stwierdzono dodatnią korela cję pomiędzy ogólną zawartością polifenoli a ogólną aktyw nością antyoksydacyjną RSA na poziomie r = 0,768 (ryc.…”
Section: Dyskusjaunclassified
“…The flavonoid glycosides confer antioxidant properties to ginkgo particularly at the mitochondrial level while the terpenoids act as antagonists of platelet-activating factor [45][46][47][48]. In comparison to other antioxidants such as vitamin C or vitamin E, the extracts of ginkgo can stabilize and protect mitochondrial function [49][50][51] thereby preventing oxidative damage to mitochondria [49].…”
Section: Ginkgo Bilobamentioning
confidence: 99%